2013
DOI: 10.1177/2045125312474019
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence in schizophrenia: factors influencing adherence and consequences of nonadherence, a systematic literature review

Abstract: Background: Nonadherence to medication is a recognized problem and may be the most challenging aspect of treatment. Methods:We performed a systematic review of factors that influence adherence and the consequences of nonadherence to the patient, healthcare system and society, in patients with schizophrenia. Particular attention was given to the effect of nonadherence on hospitalization rates, as a key driver of increased costs of care. A qualitative systematic literature review was conducted using a broad sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
381
1
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(448 citation statements)
references
References 45 publications
11
381
1
15
Order By: Relevance
“…The principal treatment-related correlates of non-adherence are attributable to the medications used in the treatment of most of these disorders. These medication-related factors include dosing regimen, side effect profiles, fear of addiction potentials, and concerns about drug-drug interactions (Weiden and Miller, 2001;DiBonaventura et al, 2012;Higashi et al, 2013;Caldeira et al, 2014;Eticha et al, 2015). Most studies conducted in subSaharan that addressed nonadherence among patients with psychiatric disorders principally assessed patientrelated and socio-economic factors, with little or no attempt made at looking at the medication-related factors as significant correlates of nonadherence.…”
Section: Introductionmentioning
confidence: 99%
“…The principal treatment-related correlates of non-adherence are attributable to the medications used in the treatment of most of these disorders. These medication-related factors include dosing regimen, side effect profiles, fear of addiction potentials, and concerns about drug-drug interactions (Weiden and Miller, 2001;DiBonaventura et al, 2012;Higashi et al, 2013;Caldeira et al, 2014;Eticha et al, 2015). Most studies conducted in subSaharan that addressed nonadherence among patients with psychiatric disorders principally assessed patientrelated and socio-economic factors, with little or no attempt made at looking at the medication-related factors as significant correlates of nonadherence.…”
Section: Introductionmentioning
confidence: 99%
“…La falta de adherencia a la medicación incluye una compleja gama de actitudes y comportamientos del paciente, los cuales van desde el rechazo del tratamiento hasta el cumplimiento parcial o irregular de las dosis diarias de medicación (Higashi et al, 2013). Los principales factores que se han asociado a la falta de adherencia son: 1) Insight.…”
Section: Factores Que Influyen En La Adherenciaunclassified
“…2) Pronóstico. La falta de adherencia muestra una fuerte relación con el incremento de síntomas psicóticos, periodos de remisión más largos (Higashi et al, 2013), aumento de las tasas de suicidio (Novick et al, 2010;Higashi et al, 2013;), incremento del deterioro cognitivo y peor calidad de vida (Ascher-Svanum et al, 2006). 3) Costes.…”
unclassified
“…In addition, symptom severity has been found to be highly correlated with nonadherence to medication among patients with schizophrenia (Higashi et al, 2013). Research has shown that the greater the severity of symptoms, the more likely a person with schizophrenia is to have impaired clinical insight, poor social adjustment, increased need for medication, and increased use of nicotine (Buckley et al, 2007;Krishnadas et al, 2012;Gerretsen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%